Analisis dan Koordinasi Relay Proteksi terhadap Gangguan Hubung Singkat pada Sistem Tenaga Listrik Menggunakan ETAP - Tanjung, Mhd Fajar Dwiandra; Rifqi Dwi Kurniawan; Willis Martin Sitorus; Arwadi Sinuraya; Desman Jonto Sinaga (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study analyzes the coordination of protection relays against short-circuit faults in a 20 kV distribution system using ETAP software. The research includes system modeling, short-circuit analysis, relay setting determination, and Time Current Characteristic (TCC) simulation. The results show that relay coordination meets IEC 60255 standards with a 0.3–0.5 second time margin, and fault currents are within safe limits according to IEC 60909. The protection system operates quickly, selectively, and reliably in fault isolation.